Saliva-Based Test as an Alternative Diagnosis for SARS-CoV-2 Patient - Istiati; Esa Ilham Mei Sasmita (Dentika: Dental Journal, 2023)
Respiratory system is affected by a novel type of virus known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The gold standard for its identification is the real-time reverse transcription polymerase chain reaction (rRT-PCR) test, despite being invasive and dangerous to medical workers during the sample-collecting process. However, major salivary glands including the parotid, submandibular, and sublingual, as well as smaller glands dispersed throughout the mouth cavity, release saliva, a hypotonic fluid, containing biomarkers that can be used to identify both local and systemic disorders, including SARS-CoV-2. This fluid can be utilized as a non-invasive, low-risk diagnostic test by medical professionals since it provides insights into patient's overall health. This study aims to determine the potential of saliva as a substitute for other SARS-CoV-2 diagnostic methods. The results from analysis of 5 scientific publications, showed that saliva contained SARS-CoV-2 virus RNA, making it suitable for patient diagnostic testing. Considering the results, the fluid was discovered to be an alternative diagnostic test for patient with the virus.